Pemasangan Implan Gigi 36 menggunakan Surgical Guide - Grace Limantara; Marzella Mega Lestari (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Statistics provided by the American Association of Oral and Maxillofacial Surgeons show that adults have lost at least one permanent tooth to an accident, gum disease, a failed root canal, or tooth decay. Several other adults have lost all of their permanent teeth. Therefore, the use of dental implants is very much needed. Research on dental implant designs, materials, and techniques has increased in the past few years and is expected to expand in the future due to the recent growth of the global market for dental implants and the rising demand for cosmetic dentistry. The definition of a successful implant has been refined from just achieving effective osseointegration to a precise positioning and good prosthetic outcome. To achieve such outcomes, the use of appropriate treatment planning is increasingly becoming popular. Demand from implant patients for quality and efficient treatment is increasing. Suitable treatment plans aid in placing the implants in an optimal position, as dictated by the function and aesthetics of the definitive restoration, and to avoid biomechanical complications and failure .This case report shows the accuracy of the surgical guide. If each step of this protocol is followed precisely, it is possible to deliver an optimum implant installation in terms of position and diameter and later on function at a very much reduced rate and time